Teknik V-Drill untuk Meningkatkan Kemampuan Forehand Smash Atlet PB Mitra Jaya Tengaran - Anugrah Choirul Ichsan; Pungki Indarto; Yudhi Purnama (Jurusan Pendidikan Kesehatan dan Rekreasi, 2022)
Background: Sport is an activity that is loved by many people, because it can improve physical health and become an activity that entertains themselves. One of the most popular sports is badminton. One of the techniques that need to be mastered in badminton is to do a forehand smash. Many previous studies have investigated the ability to perform forehand smashes, but there are still few studies that examine the improvement of forehand smash skills by practicing the V-drill technique. Therefore, this study aims to determine the effect of v-drill variation technique training on badminton forehand smash skills. Methods: This study used a sample of 30 badminton players at PB Mitra Jaya Tengaran. Data collection techniques using pretest and posttest questionnaires. After all the data were obtained, the Normality Test, Homogeneity Test and Paired Sample T-test were carried out with the help of SPSS. Results: In this study, it was found that the V-Drill variation technique had an effect on the badminton players' forehand smash skills and there was a significant difference between the forehand hitting abilities before and after being given V-Drill technique training where the badminton players' skills in hitting forehand smashes were better. Conclusions: after being given the V-Drill technique exercise compared to before being given the exercise.